Penggunaan Permainan Ular Tangga Sebab Akibat dalam Meningkatkan Kemampuan Kognitif pada Anak Usia Dini - Imamah, Imamah; Harmiasih, Srie (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This research aims to find out how the causal snake and ladder playing method is used to improve cognitive abilities in early childhood at SPS Al Faqih, Bogor City. The research method used is a case study. The research subjects were 16 children aged 5-6 years at SPS Al Faqih, Bogor City. The research instrument used was a cognitive ability observation sheet. Data were analyzed using interpretation of the observation results. The results of the research showed that there was an increase in children’s cognitive abilities after implementing the causal snake and ladder playing method. This shows that the causal snake and ladder playing method can be used can be used as a teaching method to improve the cognitive abilities of early childhood children.